PERKEMBANGAN MORAL ANAK DAN IMPLIKASINYA DALAM BELAJAR AGAMA - Hadini Hadini (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
Psychological principles are one of the principles that underlie the implementation of Islamic education. This means that the implementation of education must be based on child development, in this case, morals as one of the elements of human psychology are one of the main and most important elements that are cultivated and elements that must be optimized by the world of Islamic education. Although there are many books that talk about human morals, there are very few moral discussions when viewed from the stages of development. Therefore, a complete study is needed about the stages of moral development in each phase, with a complete study in each phase of its development, it is hoped that the formulation of Islamic education in optimizing the potential of reason can be designed appropriately. This study tries to describe how the level of human moral development is unique in each phase. This study also formulates the formulation of religious education in accordance with the characteristics of human moral growth.